The Impact of Leadership Style on Employee’s Satisfaction - Andi Tenri Angka; Gede Sri Darma (Universitas Pendidikan Nasional, 2016)
Based on the formulation of the problem mentioned above, the objectives of thisresearch are: 1) To know the impact of transactional leadership towards work satisfaction. 2)To know the impact of transformational leadership towards work satisfaction. 3) To know theimpact of transactional leadership towards work performance. 4) To know the impact oftransformational leadership towards work performance. 5) To know the impact or worksatisfaction towards work performance. The Discussion of the research’s result 1) effect oftransactional leadership on job satisfaction is significant; 2) effect of transformationalleadership on job satisfaction is significant, 3) transactional leadership’s effect on jobsatisfaction is significant, 4) transformational leadership’s effect on employee performance issignificant. 5) the Job satisfaction’s effect on employee performance is significant.Keywords: transactional leadership, transformational leadership, job satisfaction andperformance